1. Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx 2.Prove

  1. Prove the following identity:1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake
    1. answers icon 1 answer
    2. Heather asked by Heather
    3. views icon 766 views
  2. 1. Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx2.Prove the identity: cosx/1+sinx+1+sinx/cosx=2secx
    1. answers icon 0 answers
    2. Aliya asked by Aliya
    3. views icon 615 views
  3. Trigonometric IdentitiesProve: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
    1. answers icon 0 answers
    2. Dave asked by Dave
    3. views icon 1,425 views
  4. Simplify #3:[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
    1. answers icon 1 answer
    2. Anonymous asked by Anonymous
    3. views icon 1,057 views
  5. Q.1 Prove the following identities:-(i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii)
    1. answers icon 0 answers
    2. MATH............... asked by MATH...............
    3. views icon 974 views
  6. Q.1 Prove the following identities:-(i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii)
    1. answers icon 1 answer
    2. MATHS asked by MATHS
    3. views icon 1,124 views
  7. Prove the following functions:(sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/sinx)+(sin3x/cosx)=2cot2x tan2x=(2/cotx-tanx) theses are
    1. answers icon 2 answers
    2. jared asked by jared
    3. views icon 1,077 views
  8. prove the identity(sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2)
    1. answers icon 0 answers
    2. JungJung asked by JungJung
    3. views icon 894 views
  9. Prove the identity: cosx/1-tanx +sinx/1-cotx
    1. answers icon 1 answer
    2. Aliya asked by Aliya
    3. views icon 594 views
  10. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
    2. Jon asked by Jon
    3. views icon 899 views